SCHOOL BULLYING PREVENTION: IMPLEMENTATION OF THE TEACHING PERSONAL AND SOCIAL RESPONSIBILITY MODEL IN PHYSICAL EDUCATION - Oman Hadiana; Sartono (STKIP Melawi, 2026)
Abstract: This study is motivated by the high prevalence of bullying cases among elementary school students in Indonesia. It aims to implement the Teaching Personal and Social Responsibility (TPSR) model as a preventive strategy against bullying behavior in Physical Education (PE). The research employed an experimental method using a randomized posttest-only control group design. The participants were 83 fifth-grade students, consisting of 42 students in the experimental group who received TPSR instruction and 41 students in the control group who experienced conventional teaching. Data were collected using a Likert-scale questionnaire to assess bullying behavior. The data were analyzed through an independent samples test. The findings indicate that the implementation of TPSR in PE enhances students’ respect for others, empathy, social awareness, assertiveness, and willingness to assist peers facing learning difficulties. In conclusion, the TPSR model is an effective preventive approach to reducing bullying behavior among elementary school students in PE contexts. Keywords: bullying, elementary school, care, physical education Abstrak: Penelitian ini dilatarbelakangi oleh tingginya kasus perundungan di lingkungan sekolah dasar di Indonesia. Studi ini bertujuan mengimplementasikan model Teaching Personal and Social Responsibility (TPSR) sebagai upaya preventif terhadap perilaku perundungan dalam pembelajaran Pendidikan Jasmani. Metode yang digunakan adalah eksperimen dengan desain posttest-only control group secara acak. Subjek penelitian terdiri atas dua kelas V sekolah dasar dengan total 83 siswa, di mana 42 siswa sebagai kelompok eksperimen memperoleh pembelajaran TPSR, sedangkan 41 siswa sebagai kelompok kontrol menggunakan pendekatan konvensional. Instrumen pengumpulan data berupa kuesioner skala Likert untuk mengukur perilaku perundungan. Analisis data dilakukan menggunakan uji sampel independen. Hasil penelitian menunjukkan bahwa penerapan TPSR mampu meningkatkan sikap menghargai orang lain, empati, kepedulian sosial, ketegasan, serta kemampuan membantu teman. Dengan demikian, TPSR efektif sebagai strategi pencegahan untuk meminimalkan perilaku perundungan pada siswa sekolah dasar. Kata Kunci: Perundungan, sekolah dasar, peduli, pendidikan jasmani